2013
DOI: 10.1007/s00520-013-1918-0
|View full text |Cite
|
Sign up to set email alerts
|

Rest/activity rhythm is related to the coexistence of pain and sleep disturbance among advanced cancer patients with pain

Abstract: The rest/activity rhythm influences the coexisting pain and sleep disturbances. Pain functions as a complete mediator in their relationship. Interventions that improve rest/activity rhythms may improve the management of pain and sleep disturbances in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…This study is part of a large-scale investigation, the results of which have previously been published (Ma et al, 2014). From the oncology ward of a teaching hospital in Taiwan, we collected data related to 68 cancer patients experiencing pain who were hospitalized for various cancer treatment regimens and the control of symptoms between August 2006 and October 2007.…”
Section: Study Design and Samplementioning
confidence: 99%
See 4 more Smart Citations
“…This study is part of a large-scale investigation, the results of which have previously been published (Ma et al, 2014). From the oncology ward of a teaching hospital in Taiwan, we collected data related to 68 cancer patients experiencing pain who were hospitalized for various cancer treatment regimens and the control of symptoms between August 2006 and October 2007.…”
Section: Study Design and Samplementioning
confidence: 99%
“…Pain and other related symptoms experienced by cancer patients can affect their rest-activity rhythms (Innominato et al, 2009a;Ma et al, 2014). Numerous studies have demonstrated that disruptions in restactivity rhythm can have negative consequences for cancer patients and jeopardize survival (Innominato et al, 2009a(Innominato et al, , 2012Mormont et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations